أسلوب التوكيد في القرآن الكريم وتطبيق اتو عند المفسرين من خلال تفسير الكشاف للزمخشري - العقبي, ابتسام; بن عيشة, عائشة; لعويد, هدى (جامعة الوادي university of eloued, 2019)
يعد أسلوب التوكيد من أساليب اللغة الع ربية التي يراد بها تقوية ات١عتٌ كتثبيتو كإزالة الشك كترسيخ اليقتُ في ذىن ات١خاطب كقد ناؿ موضوع التوكيد كأسلوبو حظا كفتَا من دراسات البلاغيتُ كالنحويتُ على حد سواء. كيتناكؿ ىذا البحث " أسلوب التوكيد كتطبيقاتو عن الإما الزت٥شرم " كقد تضمن فصلتُ إحدت٫ا نظرم كالآخر تطبيقي. تضمن النظرم مطالب تتعلق بتًتٚة الإما الزت٥شرم ككتابو كبأسلوب التوكيد كأدكاتو، كأما الفصل التطبيقي فقد جاءت الدراسة منتصبة على كتاب الكشاؼ. بٍ كانت ات٠ات٘ة التي تضمنت ت٣موعة من نتائج الدراسة كقد توصلنا إلى النتيجة التالية: أفٌ الغرض كات٢دؼ اتٟقيقي لاستخدا التوكيد في القرآف الكرنً ىو رفع احتمالية توىم أك إزالة التوىم من خلاؿ السياؽ.The emphasizing is on of arabic laguage method which intedee to strengthening the meaning، comfirme it، remove uncertanty and anchoring the certainty in the mind of the addressed، The subject of assertion and its style has received a .lot of the linguists and grammarians’ surveys. This search had "the emphasizing an its applications with El-imam El Zamakhshari " this has included two chapters، one is theorical and the othercis practical The theorical include demands relating with El-imam El Zamakhshari's translation، his whriting and the emphasizing and it's tools، but the practical one، the study was erect on the book of El Kashef. In the conclution ، there was a set of results of the studies، The real objective of using the assertion in the Holy Quran is rising the allusion possibility or removing the allusion through the context.
لغة